ARTICLE ON EFFECT OF MANJISTHA IN SKIN CARE WSR AYURVEDA CONTEXT - Dr. Suresh Kumar Jat, Dr. Shikha Sharma (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2019)
Ayurveda is an ancient medical science originated in India. Since the early age, human life has a great impact on the external appearance of an individual. Skin is the basic element of the external appearance. Beauty is generally depended on the type and texture of the skin one has. Ayurveda determined beauty by prakriti, sara, sanhana, pramana, twakand dirghayulakshana. The concept of using herbs for beautification is well defined in Ayurveda. The cosmetic preparations are used for worship and for sensual enjoyment in India since Vedic period.Cosmetology is the science of alternation of appearance and modification of beauty.Ayurvedacosmetology starts from dinacharyaand ritucharyawith the use of herbal medicines. Ayurvedacharyasbelieve that toxins (imbalanced doshas) inside the body makes the person unhealthy and the unhealthy body leads to unhealthy skin (dull skin) etc. .Manjistha is considered to be one of the most valuable herbs in Ayurveda, the world’s oldest health care system that originated in India. KEYWORDS -Ayurveda cosmetology,Beauty, Manjistha, Skin care.